Suitability Study of Using UAVs to Estimate Landfilled Fly Ash Stockpile - Kuinkel, Muskan Sharma; Zhang, Chengyi; Liu, Peng; Demirkesen, Sevilay; Ksaibati, Khaled (Mdpi, 2023)
The decrease in fly ash production due to the shift in coal industries toward a green environment has impacted many concrete industries as fly ash is a significant component in cement and concrete. It is critical for concrete industries to identify the availability of fly ash in landfills to meet their demand if the supply decreases. This paper aims to analyze the suitability of UAVs in determining the fly ash stockpile volumes. A laboratory test is performed to validate the proposed UAV method. Then, a real quarry site is selected to demonstrate the suitability in a large scale. The results indicate that the UAVs estimate the most accurate volume of the stockpile when the flight height is about five times the stockpile height. A considerable range of 3.5-5 times the stockpile height is most suitable for quantity takeoff. The findings of this study provide a recommendation for choosing the most appropriate technology for the quantitative estimation of fly ash in existing landfills on a large scale.
Keywords: UAVs; stockpile; volumetric analysis